PERENCANAAN DINDING PENAHAN TEBING JALAN PADA RUAS JALAN MALANG-KEDIRI (12 KM) DI DESA MULYOREJO KECAMATAN NGANTANG KABUPATEN MALANG - Makleat, Antonio Luis; Sulistyani, Kiki Frida; Arifianto, Andi Kristafi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Retaining wall is an important component of the main building structure for building highways and other environmental related contoured land or land that has a different elevation. Briefly retaining wall is a wall built to restrain land mass above the structure or building made. Type retaining wall used in this study is a gravity type retaining wall, The purpose of this study to determine the condition of the soil, causing the collapse of the retaining wall, analyze the planning retaining wall and determine the stability of the retaining wall on the street segment Malang Kediri STA 12 Km In the village Mulyorejo. Type retaining wall planned to use the back side of the retaining wall skewed because of this type in accordance with the height of the river. Retaining wall dimensions b = 5m,h = 8 m, stable against: the soil bearing capacity = 114.255> qa = 89.404 (secure), Steady against the wall shear = 1.66> 1.5 (secure) stable against the wall bolsters style = 2.05> 1.5 (secure). Keywords: Strong safety factor of soil bearing, sliding and rolling.